MICROPROPAGATION STUDY ON THREE VARIETIES OF ZINGIBER OFFICINALE ROSE. - Azmi Muda, Mohd.; N, Khalid; Ibrahim, Halijah (Malaysian Journal of Science, 2004)
The in vitro propagation protocols for three varieties of Zingiber officinale were successfully established in this study. Averages of three to five shoots per explant were successfully regenerated on MS medium supplemented with 3.0% (w/v) sucrose, 0.2% (w/v) phytagel, and 1.0-3.0 mg/l BAP. All varieties studied have shown that the rhizome yield from in vitro plantlets were higher than those from in vivo materials. The protocols developed can be adopted for propagation and conservation purposes.